(untitled) (Scientific journal of the Fergana State University, 2025)
The article presents scientific data on micro- and macro-aggregation of soils distributed in the Konimekh natural geographical region. According to the general analysis, when looking along the profile of the studied soils, in the main cases from the top to the bottom layers, “very poor” (>60%), “unsatisfactory” (40-60%), “satisfactory” (25-40%), “good” (15-25%) and “very good” (<15%) microstructures were formed. It is based on the periodicity of irrigation and the level of cultivation in the irrigated gray-brown and gray brown-meadow soils developed in the areas of irrigated agriculture compared to the sandy desert soils.